Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.3402/polar.v30i0.15469
|View full text |Cite
|
Sign up to set email alerts
|

Some like it cold: microbial transformations of mercury in polar regions

Abstract: The contamination of polar regions with mercury that is transported from lower latitudes as inorganic mercury has resulted in the accumulation of methylmercury (MeHg) in food chains, risking the health of humans and wildlife. While production of MeHg has been documented in polar marine and terrestrial environments, little is known about the responsible transformations and transport pathways and the processes that control them. We posit that as in temperate environments, microbial transformations play a key rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 172 publications
(163 reference statements)
0
25
0
Order By: Relevance
“…Methylmercury (MeHg), mercury (Hg) most toxic form, bioconcentrates in organisms and biomagnifies along the aquatic food chains (Clarkson and Magos 2006). Although MeHg concentrations in sediments can be affected by exchanges with the water column, the main controlling factor of these concentrations appears to be the balance between Hg II in situ methylation and MeHg demethylation reactions, two opposite natural processes primarily mediated by aquatic microorganisms (e.g., Ullrich et al 2001; Barkay et al 2011;Gilmour et al 2011;Yu et al 2012). Despite some early laboratory experiments which suggested that Hg II methylation results from the activity of many aerobic and anaerobic microorganisms (Jensen and Jernelöv 1969;Vonk and Sijpesteijn 1973), more recent researches showed that methylation capacity in aquatic sediments is limited to anaerobic bacteria, including sulfate-reducing bacteria (SRB) Bartha 1984 and1985;Choi et al 1994;Baldi 1997), iron-reducing bacteria (IRB) (Fleming et al 2006;Kerin et al 2006;Yu et al 2012) and methanogens (Hamelin et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methylmercury (MeHg), mercury (Hg) most toxic form, bioconcentrates in organisms and biomagnifies along the aquatic food chains (Clarkson and Magos 2006). Although MeHg concentrations in sediments can be affected by exchanges with the water column, the main controlling factor of these concentrations appears to be the balance between Hg II in situ methylation and MeHg demethylation reactions, two opposite natural processes primarily mediated by aquatic microorganisms (e.g., Ullrich et al 2001; Barkay et al 2011;Gilmour et al 2011;Yu et al 2012). Despite some early laboratory experiments which suggested that Hg II methylation results from the activity of many aerobic and anaerobic microorganisms (Jensen and Jernelöv 1969;Vonk and Sijpesteijn 1973), more recent researches showed that methylation capacity in aquatic sediments is limited to anaerobic bacteria, including sulfate-reducing bacteria (SRB) Bartha 1984 and1985;Choi et al 1994;Baldi 1997), iron-reducing bacteria (IRB) (Fleming et al 2006;Kerin et al 2006;Yu et al 2012) and methanogens (Hamelin et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, environmental incubations also suggested that SRB and IRB are the main mercury methylators in natural environments (Gilmour et al 1992(Gilmour et al , 2011Yu et al 2010Yu et al , 2012Acha et al 2012), with SRB being the dominant community (Choi et al 1994;Baldi 1997;Pak and Bartha 1998;Yu et al 2010). On the other hand, MeHg demethylation results from numerous types of microorganisms in both aerobic and anoxic environments (Oremland et al 1991;Dahlberg and Hermansson 1995;Pearson et al 1996;Marvin-Dipasquale and Oremland 1998;Marvin-Dipasquale et al 2000), either by reductive or oxidative demethylation (Barkay et al 2011;Mason 2012). In oxidative demethylation, active in SRB and methanogens, MeHg is converted into Hg II , whereas in reductive demethylation, more extensively distributed throughout microbial communities, MeHg is converted into Hg 0 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they concluded that merA ‐mediated activity could account for up to 90% of Hg 0 production at a greater depth in the water column. In fact, mer induction should not only depend on absolute Hg concentrations but also other factors that affect actual Hg bioavailability to bacteria (Barkay et al ). Our results showed that bacteria still exhibited significant capacity to produce Hg 0 at ambient concentrations as low as ~5 pM.…”
Section: Discussionmentioning
confidence: 99%
“…The Hg-resistance gene, merA, is considered broadly distributed among bacteria and archaea probably due to horizontal gene transfer in evolution (Osborn et al 1997;Boyd and Barkay 2012), but the prevalence of Hg-resistance among bacteria can vary from one location to another (Barkay et al 2011). Further investigations using metagenomic analysis could elucidate the microbial community composition in SSW and LIW.…”
Section: Comparison Of Hg 0 Formation Between Ssw and Liwmentioning
confidence: 99%
“…Hg is then removed by particles and snow and is deposited on the landscape or water surfaces (Kirk et al 2012). Specific microorganisms in the aquatic environment are able to convert inorganic Hg (iHg) into organic derivatives, such as mono-methylmercury (MeHg) and dimethylmerury (Barkay et al 2011, King et al 2001, Lehnherr et al 2011, Parks et al 2013, Pongratz and Heumann 1999. However, experiments suggest that di-methylmercury is not bioaccumulated by phytoplankton (Mason et al 1996).…”
Section: Introductionmentioning
confidence: 99%